2017
DOI: 10.1093/chemse/bjx071
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Taste Perception and Spicy Preference: A Thai–Japanese Cross-cultural Study

Abstract: Taste perception is influenced by several factors. However, the relation between taste perception and food culture is unclear. This study compared taste thresholds between populations with different food culture, i.e. Thai and Japanese. A matched case-control study was conducted in 168 adults (84 for each; aged between 50 and 90 years). The age, sex, systemic disease, medication, smoking, xerostomia, and oral hygiene of both groups were not different. Recognition thresholds (RTs) of sweet, salty, sour, bitter,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 30 publications
2
28
0
Order By: Relevance
“…This could be due to differences in the taste of the usual food consumed daily. The Sri Lankan students primarily ate very spicy Sri Lankan-style curries every day, and the habit of eating spicy food possibly lowers the sensitivity of taste [13]. Another possible explanation for the lower taste scores among the Sri Lankan students in the present study could be related to blood zinc concentrations.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…This could be due to differences in the taste of the usual food consumed daily. The Sri Lankan students primarily ate very spicy Sri Lankan-style curries every day, and the habit of eating spicy food possibly lowers the sensitivity of taste [13]. Another possible explanation for the lower taste scores among the Sri Lankan students in the present study could be related to blood zinc concentrations.…”
Section: Discussionmentioning
confidence: 65%
“…In mammals, taste is generally divided into 5 basic qualities, namely salty, sweet, bitter, sour, and umami, as well as overall "deliciousness" [6,7]. Previous studies have elucidated that these tastes are affected by various factors, including age [8], systematic diseases, decreased salivary flow, nutrition (including micronutrient deficiency) [9,10], oral hygiene [11], and differences in dietary habits due to country of residence [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, intense spiciness in dipping sauce was a negative driver for UAE consumers, and spiciness intensity was not a critical factor for US and KOR consumers when spiciness was the dominant flavor property. Among the various sensory attributes, spiciness shows the widest variation in individual preference for its presence or intensity level in foods [ 47 , 48 , 49 ]. This diversity in preference for chili spiciness is due to factors such as diversity in cultural exposure to the flavor, genetic influence, gender, and personal traits.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly lower scores were found in 6 domains when compared to healthy population, including physical function (p<0.0001), role-physical (p<0.0001), bodily pain (p=0.0005), general health (p<0.0001), vitality (p<0.0001), and role-emotional (p<0.0001). Smell only and combined smell and taste 30 reported that Thai people have a strong preference for spicy food, with a preference for mild-moderate spicy food in 70%, and very spicy food in 10% of respondents. That study also found that 70% of Thai people consumed spicy food on a weekly basis.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that populations with a preference for hot and spicy foods, such as Thailand, may have much poorer taste sensitivity and perception. 30 Another reason that SF-36 (Thai version) scores were significantly lower in patients with taste defect may be due to the small number of patients in the taste disorder group. Future study in a larger study population is, therefore, recommended-especially since problems with taste were found to have the most adverse effect on QoL.…”
Section: Discussionmentioning
confidence: 99%